Management of Collaboration between Schools and Communities in Play Group Management Efforts - Ita, Efrida; Ngura, Elisabeth Tantiana; Landang, Maria Fatima (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
This study aims to describe: 1) the management of cooperation between the school and the community of West Nginamanu village in an effort to manage the childhood education in St. Hildegard Ize playgroup, and 2) the supporting and inhibiting factors in the management of cooperation between school and community in an effort to manage the childhood education in St. Hildegard Ize group play Wolomeze district, Ngada regency. This study used a qualitative approach and located in St. Hildegard Ize playgroup Wolomeze district. The subject of the study were the group play manager, parents, and village officials. Data collection was done through interviews, observation, and documentation. Data analysis used an interactive model from Miles and Huberman with its components, namely data reduction, data presentation, and conclusion drawing. The results show that 1) the cooperation management between the school and the members of the community in St. Hildegard Ize playgroup that seen from the planning, organizing, implementation, and controlling has been run well, but at the implementation stage it is still not optimal, 2) The hindering factors for cooperation between the school and the community namely the condition of parents’ occupation, the improper building condition of St. Hildegard Ize playgroup, and the incapable teachers in communicating the children’s development to the parents, whereas the supporting factors namely the parents’ concern towards the early childhood education and the school’s openness in receiving input from the parents.